ON THE ISSUE OF THE IMPORTANCE, TASKS AND FUNCTIONS OF CONTROL OVER THE ACTIVITIES OF BUSINESS ENTITIES ENGAGED IN THE TRANSPORTATION OF PASSENGERS BY ROAD (Bulletin of criminological association of Ukraine, 2024)
The article emphasizes in the context of understanding the importance of control over the activities of business entities engaged in passenger transportation by road in Ukraine that the latter is an important mechanism for maintaining high standards of safety and quality of transport services. The state, by implementing a systematic and digitalized approach to control, ensures not only compliance with current legislation, but also adaptation to European standards. As a result, effective control in this area has a positive impact on road safety, economic development and well-being of citizens of Ukraine. It is argued that the tasks of control over the activities of business entities engaged in passenger transportation by road should be understood as goals and actions aimed at verifying and ensuring compliance with legislative norms and standards by business entities engaged in passenger transportation. The main tasks of control over the activities of business entities in the field of passenger transportation are to verify compliance with licensing requirements, analyze the technical condition of vehicles, monitor compliance with traffic schedules and transportation schedules, monitor compliance with drivers' labor standards, and also check compliance with transportation tariffs. It is emphasized that control functions are stable complexes of actions that are performed within the framework of the management system in order to ensure the achievement of organizational goals, maintain order and control over the implementation of plans. Their implementation is possible subject to monitoring, which involves regular observation of the activities of enterprises in the field of transportation in order to identify violations; assessment, which consists in analyzing the results of the activities of business entities to determine their compliance with legislative requirements and quality standards; regulation, which includes the development and implementation of regulatory legal acts. The main control functions are monitoring, evaluation, feedback, adjustment, preventive control and the formation of standards. Control functions also include audit, administrative, sanctioning and preventive functions.
Keywords: meaning; tasks; functions; control over the activities of business entities; administrative and legal regulation; passenger transportation by road